Design and Potential of Halal Tourism Industry in Yogyakarta Special Region - Ahmad Nurozi (Journal of Islamic Economics Lariba, 2021)
This study discusses the Analysis of the Potential of the Halal Tourism Industry in the Special Region of Yogyakarta. As a student city and tourism city, Yogyakarta has various tourism potentials that developed to the fullest, such as based on the religious background of its visitors, especially for Muslims. This research aims to find out the possibility of the halal tourism industry in the Special Region of Yogyakarta, explain the industry's concept, and find out its development strategy. The urgency of this research is to map and develop the potential of halal tourism in the Special Region of Yogyakarta and to design the design of the halal tourism industry based on local wisdom values that do not substantively conflict with Islamic law. In addition, to provide a new paradigm in the tourism industry system that still prioritizes comfort based on the values of belief held by tourists. This research is field research in various Yogyakarta tourism areas with a normative - sociological - phenomenological approach. Primary and secondary data sources are obtained through field studies and through document studies related to research using content analysis of research instruments are the researchers themselves. The study results found that there were several religious tourism objects and various other tourist objects that had indirectly applied some of the principles of the sharia tourism industry. The existence of several sharia hotels supports this to increase the attractiveness of Muslim tourists to visit DIY. To further increase the existing potential, it is necessary to have a local government regulation that explicitly regulates the existence of the sharia tourism industry, as has been done by the local government of Lombok, West Nusa Tenggara.